Development of an imaging system for visualization of Ebola virus glycoprotein throughout the viral lifecycle - Furuyama, Wakako; Sakaguchi, Miako; Yamada, Kento; Nanbo, Asuka (Frontiers in Microbiology, 2022)
Ebola virus (EBOV) causes severe EBOV disease (EVD) in humans and non-human primates. Currently, limited countermeasures are available, and the virus must be studied in biosafety level-4 (BSL-4) laboratories. EBOV glycoprotein (GP) is a single transmembrane protein responsible for entry into host cells and is the target of multiple approved drugs. However, the molecular mechanisms underlying the intracellular dynamics of GP during EBOV lifecycle are poorly understood. In this study, we developed a novel GP monitoring system using transcription- and replication-competent virus-like particles (trVLPs) that enables the modeling of the EBOV lifecycle under BSL-2 conditions. We constructed plasmids to generate trVLPs containing the coding sequence of EBOV GP, in which the mucin-like domain (MLD) was replaced with fluorescent proteins. The generated trVLP efficiently replicated over multiple generations was similar to the wild type trVLP. Furthermore, we confirmed that the novel trVLP system enabled real-time visualization of GP throughout the trVLP replication cycle and exhibited intracellular localization similar to that of wild type GP. In summary, this novel monitoring system for GP will enable the characterization of the molecular mechanism of the EBOV lifecycle and can be applied for the development of therapeutics against EVD.